2016
DOI: 10.1111/mec.13517
|View full text |Cite
|
Sign up to set email alerts
|

Climate variables explain neutral and adaptive variation within salmonid metapopulations: the importance of replication in landscape genetics

Abstract: Understanding how environmental variation influences population genetic structure is important for conservation management because it can reveal how human stressors influence population connectivity, genetic diversity and persistence. We used riverscape genetics modelling to assess whether climatic and habitat variables were related to neutral and adaptive patterns of genetic differentiation (population-specific and pairwise FST ) within five metapopulations (79 populations, 4583 individuals) of steelhead trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 87 publications
(153 reference statements)
2
42
1
Order By: Relevance
“…This approach is considered beneficial because ensuing models will have better predictive power, which may be tested internally with a subset of the data, or externally with independent data (Hand et al. ; Richardson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is considered beneficial because ensuing models will have better predictive power, which may be tested internally with a subset of the data, or externally with independent data (Hand et al. ; Richardson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…References to less recent studies can be found in several review papers (Hemmer‐Hansen et al , ; Pujolar et al , , ; Ulrik et al , ; Willette et al , ; Gaither et al , ; Guo et al , ; Elmer, ; Picq et al , , as well as references in the next section as examples of the most recent studies). In contrast, fewer fish studies have used a landscape genomic framework to detecting selection by finding statistical associations between local allele frequencies and environmental variables and those have mainly been performed on salmonids (Zueva et al , ; Hecht et al , ; Hand et al , ). For instance, Hecht et al () used RADseq to genotype nearly 2000 Chinook salmon Oncorhynchus tshawytscha (Walbaum 1792) from 46 localities at about 20 000 SNPs in order to document environmental adaptation throughout the North American range of the species, from California to Alaska.…”
Section: Modern Approaches To Study Genomics Of Local Adaptationmentioning
confidence: 99%
“…Landscape features can shape both neutral genetic structure and the distribution of adaptive variation within a species (Davis, Epps, Flitcroft, & Banks, ; Grummer et al, ; Orsini, Andrew, & Eizaguirre, ). While landscape genetic studies in rivers increasingly consider adaptive variation (Brauer, Unmack, Smith, Bernatchez, & Beheregaray, ; Micheletti, Matala, Matala, & Narum, ; Vincent, Dionne, Kent, Lien, & Bernatchez, ), few studies have directly compared patterns of neutral genetic variation with patterns of variation at loci associated with adaptive phenotypic variation (but see Hand et al, ; Keller, Taverna, & Seehausen, ; O’Malley, Jacobson, Kurth, Dill, & Banks, ). This comparison could improve our understanding of the mechanisms that either facilitate or restrict gene flow in the face of selection and adaptive divergence on life history characteristics (e.g., migratory vs. resident life histories) in fragmented river networks and landscapes.…”
Section: Introductionmentioning
confidence: 99%